Extreme weather is disrupting lives in southern Africa: New policies are needed to keep the peace - Maviza, Gracsious; Gadu, Siyaxola (2024)
Over the past decades, heavy and more frequent rainfall and dry spells in southern Africa have caused loss and damage to agriculture, livestock, the energy sector, food security and nutrition. Gender and migration scientist Gracsious Maviza and climate change specialist Siyaxola Gadu talked to The Conversation Africa about how this poses risks to stability and peace in the region.